PERLINDUNGAN HUKUM HAK ANAK SEBAGAI KORBAN PERUNDUNGAN (BULLYING) DI KOTA PONTIANAK (STUDI SEKOLAH PONTIANAK TIMUR) - NIM. A1011211181, CATRINE MANURUNG (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This type of research is empirical legal research with a descriptive nature. Data or legal materials used are primary data and secondary data. The data collection techniques used were interviews, observation, and documentation. The approach used is a qualitative approach. Regulations regarding the legal protection of children